Analysis of Job Competency Needs of Computer and Information Engineering Program by Referring to KKNI in Vocational Schools - Ashabul Taufik; Purnamawati Purnamawati; Abdul Muis Mappalotteng (PT ARRUS Intelektual Indonesia, 2023)
This study aims to determine (1) the need for work competency in Computer and Network Engineering Skills Package based on the KKNI. (2) The relevance level of Computer and Network Engineering Expertise Package based on KKNI. This type of research uses a mixed method approach to the Concurrent Embedded Design model, using data collection techniques of observation, interviews, essays, triangulation and questionnaires. The results of the study indicate that the work competency requirements of the TKJ SMKN Makassar City expertise package refer to KKNI: 1) Preparing the optical fiber supporting tools and materials; 2) Installing fiber optic cable networks; 3) Carry out fiber optic network cable tester; 4) Configuring the management switch on the network; 5) Designing network topology; 6) Configuring routing on network devices in an autonomous system; 7) Change the device according to your needs; 8) Routing using a Cisco router. The relevance level of the competency package of TKJ SMKN Makassar City referring to KKNI shows an average score of 116.32 in the Very Relevant category. The percentage frequency with a value of 52% states the Relevant category and the frequency of a percentage with a value of 48% in the Very Relevant category. Based on these results, the Computer and Network Engineering expertise package of the Makassar City Vocational School reforms the equipment and practice materials of the computer network and meets the competency needs of the TKJ expertise package to achieve work competency based on the KKNI